ANALISIS PERBUATAN MENGHALANGI PROSES PENYIDIKAN, PENUNTUTAN DAN PERADILAN (OBSTRUCTION OF JUSTICE) DALAM SISTEM PIDANA DI INDONESIA - Suryadi, Mohammad Anton; Zainal, Muhammad (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
ABSTRACT Obstruction of justice or what is betterly known as the acts of obstructing to the judicial process is a type of crime because its action is considered to hamper the law enforcement system and damage to the image of law institutions. The obstruction of justice aims to obstruct or have effect to pervert the legal process and to disrupt the proper function of a judicial process. Another definition of obstruction of justice is an attempt to interfere with the administration of the courts, the judicial system or law enforcement officers, including threatening witnesses, inappropriate conversations with the jury (judge), hiding evidence, or interfering with the arrest process. Therefore, the obstruction of justice is considered as any types of intervention to the entire legal and justice process from beginning till ending. Therefore, the obstruction of justice is categorized as a type of criminal acts of the contempt of court. The criminal law system of Indonesia normatively regulates acts of obstructing the justice process in many regulations, both generally in the penal code and the specific criminal laws that regulate the eradication of corruption, the eradication of terrorism, the eradication of human trafficking, prevention and eradication of money laundering and narcotics law. The point that needs to be paid attention to regarding acts of obstructing the judicial process in the penal code is that of many articles that can be analogous as the acts of obstructing the judicial process, there are 2 (two) articles that clearly state the elements of preventing, obstructing, thwarting, causing trouble, obstructing the judicial process. The same elements have also been regulated in the articles which constitute as the acts of obstructing to the judicial process in the specific criminal laws. Keywords: the acts of obstructing to the judicial process, Criminal System of Indonesia